Appeals to the judicial committee of the privy council / Rashidah Abu Bakar - Abu Bakar, Rashidah (Faculty of Law, 1978)
In this exercise, the writer in Chapter I deals mainly with the historical aspect of appeals to the Judicial Committee and a summary of the nature of work carried out. The writer also devotes some time to a discussion of the historical and practical similarities and differences between the House of Lords and the Judicial Committee. In Chapter II, discussion is centred around statutory provisions and agreements regulating the procedure of appeals to the Judicial Committee. The writer also traces the development of such statutes and agreements as are relevant to the study. In relation to this, the writer includes some mention of the period during which Singapore was part of Malaysia. From the available reports of appeals to the Judicial Committee, the writer was also able to obtain some statistics which are laid out in Chapter III. In the final Chapter of this exercise, the writer also looks into the trend of other Commonwealth countries in relation to the abolition of appeals.. Recognition is also taken of the fact that the Judicial Committee, despite the many criticism against it, has played a major role as the Commonwealth court of appeal.